MOSSBAUER SPECTROSCOPIC EVIDENCE FOR NONEQUIVALENT SITES OF IRON ATOMS IN GOLD-BEARING ARSENOPYRITE - Murzin V.V.; Semenkin V.A.; Pikulev A.I.; Mil'der O.B.; Sustavov S.G.; Krinov D.I. (My University, 2003)
Eight samples of arsenopyrite from the Kochkar (Southern Urals) and Nezhdaninskoe (Siberia) deposits were studied by the method of Fe-57 Mossbauer spectroscopy. The mineral samples showed considerable variations in arsenic and sulfur contents, S/As = 0.98-1.25. According to INAA data, the arsenopyrite contains up to 343.7 ppm Au, and more than 95% of the gold in the Nezhdaninskoe deposit is chemically bound [6]. The Fe-57 Mossbauer spectra of arsenopyrite from the Kochkar deposit are interpreted as a superposition of three quadrupole doublets, and the spectra of the Nezhdaninskoe arsenopyrite also contain an additional singlet component. With respect to Is and Qs values (mm/s, Is = 0.238-0.276, Qs = 1.096-1.13; Is = 0.25-0.36, Qs = 0.59-0.79; and Is = 0.223-0.278, Qs = 1.32-1.55), the doublets are identical or similar to the published data for arsenopyrite FeAsS, pyrite and/or marcasite FeS2, and loellingite FeAs2, In the Kochkar deposit, a regular increase in Is and a decrease in Qs were observed for all three iron positions described by the doublets with increasing interplanar distance d(202) and S/As of arsenopyrite. It was supposed that each of them can be presented as a combination of polyhedra with a certain population of S and As atoms dissolved in the arsenopyrite structure and not forming their own mineral phases. The iron position described by the singlet (Is = 0.580-0.60 mm/s) is most appropriate for its isomorphic replacement by gold.
Keywords: Mossbauer spectroscopy; Arsenopyrite